2016
DOI: 10.1093/infdis/jiw302
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Zika Virus Infection, Chiapas State, Mexico, 2015, and First Confirmed Transmission byAedes aegyptiMosquitoes in the Americas

Abstract: Background. After decades of obscurity, Zika virus (ZIKV) has spread through the Americas since 2015 accompanied by congenital microcephaly and Guillain-Barré syndrome. Although these epidemics presumably involve transmission by Aedes aegypti, no direct evidence of vector involvement has been reported, prompting speculation that other mosquitoes such as Culex quinquefasciatus could be involved.Methods. We detected an outbreak of ZIKV infection in southern Mexico in late 2015. Sera from suspected ZIKV-infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
145
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(159 citation statements)
references
References 34 publications
8
145
2
1
Order By: Relevance
“…Recent reports have shown that Aedes aegypti mosquitoes are highly competent vectors for American isolates of ZIKV (10). In addition, A. aegypti was found to be the primary vector for ZIKV in southern Mexico (11). Mouse models for ZIKV neuropathogenesis and in utero transmission have recently been reported in mice deficient in innate immune responses by using African and Asian genotype isolates (12)(13)(14)(15), though there have not been in vivo pathogenesis studies using an isolate from the American outbreak.…”
mentioning
confidence: 99%
“…Recent reports have shown that Aedes aegypti mosquitoes are highly competent vectors for American isolates of ZIKV (10). In addition, A. aegypti was found to be the primary vector for ZIKV in southern Mexico (11). Mouse models for ZIKV neuropathogenesis and in utero transmission have recently been reported in mice deficient in innate immune responses by using African and Asian genotype isolates (12)(13)(14)(15), though there have not been in vivo pathogenesis studies using an isolate from the American outbreak.…”
mentioning
confidence: 99%
“…Given the urgent need to increase our understanding of ZIKV, we asked whether RPLP1/2 are also required for ZIKV infection. We analyzed ZIKV isolates of the American lineage (isolate MEX_I_7) (33) and African lineage (isolate 41525) (34). To this end, we knocked down RPLP1/2 in A549 and HuH-7 cells and then infected the cells at an MOI of 1.…”
Section: Resultsmentioning
confidence: 99%
“…For example, mosquitoes carry other insect-specific viruses including flaviviruses, which could easily lead to misleading conclusions about the presence of ZIKV using microscopy and even immunofluorescence labelling approaches. Moreover, natural infection in domestic Culex mosquitoes have never been found nor convincingly demonstrated in surveys conducted in ZIKV endemic and epidemic areas [12,13,62,63].Although mosquitoes of the Cx. pipiens complex are known spreaders of infectious agents including arboviruses, the flavivirus St Louis encephalitis virus or the alphavirus Sindbis virus [27,28], we suggest that this is not the case for ZIKV which belongs to the Spondweni serogroup with Spondweni virus, and both flaviviruses are transmitted by Aedes spp.…”
mentioning
confidence: 99%
“…An enzootic cycle limited to Africa and Asia with occasional spillover events has been described [10,11]. In the current outbreak in the Americas, ZIKV is believed to be mainly transmitted by the human-biting mosquito Aedes aegypti [12,13]. Whether a similar enzootic cycle in the Americas can be established is not known and it has been suggested that such a process would make eradication efforts 'practically impossible' [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation